P103 Identifying CES-1 positive myeloid cells with mass cytometry as a potential therapeutic target for Crohn's disease. (21st January 2022) - Hageman MD, I; Elfiky, A; Becker, M; Joustra, V; Buskens, C; Li Yim, A; Hakvoort, T; Verhoeff, J; Garcia Vallejo, J; D'Haens, G; Wildenberg, M; De Jonge, W
Abstract: Background: Myeloid cells are key players in the sustained inflammatory process in Crohn's disease (CD), and are therefore therapeutic targets. Human mononuclear myeloid cells express the cell selective expression of carboxylesterase 1 (CES-1). Esterase-sensitive motif (ESM) technology has been developed to specifically target ESM tagged small molecules on human mononuclear myeloid cells, based on their CES-1 expression, creating a larger therapeutic window with less side effects. This study investigates the presence of CES-1 expressing cells in PBMCs, intestinal biopsies and fistula cells of CD patients, highlighting the potential of ESM-technology in CD. This could benefit CD treatment in non-responsive patients or patients with a fistulizing phenotype. Methods: Intestinal biopsies were collected from CD patients who underwent endoscopy. PBMCs were collected from CD patients who were receiving Vedolizumab (VDZ) treatment and categorized as responders or non-responders. Criteria for response was based on clinical (HBI ≤4) and biochemical (fecal calprotectine ≤250 µg/g) and/or endoscopic assessment (≥50% reduction in SES-CD score). Fistula tissue was of CD patients was obtained during surgery. CES1-positive cells were phenotyped by mass cytometry with a panel of 32-markers, including the myeloid markers CES-1, CD14, CD16, HLA-DR, CD11c, CD206. Results: We demonstrated the presence of CD14+HLADR+CD11a+CD44+CD11b+ myeloid cells exclusively expressing CES-1 in intestinal biopsies of CD patients (n=7). CES-1 expression did not differ between inflamed and uninflamed tissue. In PBMCs of VDZ responders (n=5) and non-responders (n=6), we were able to identify different subsets of myeloid cells such as classical (CD14++CD16-), intermediate(CD14+CD16+) and non-classical (CD14-CD16++) monocytes, DCs and CD2+ DC precursors all demonstrating CES-1 expression. Percentage of CES-1 positive cells in inflamed PBMCs (or non-responders) was higher than in uninflamed PBMCs (responders) in all of the above-mentioned subsets. Furthermore, we demonstrated different myeloid populations within fistula cells (n=13) such as pDCs (CD123+CD68+HLA-DR+), DCs (CD11c+CD11b+HLA-DR+ CD44+), CD141+DCs (CD141+CD49d+HLA-DR+), Macrophage (CD14+CD11c+CD11b+HLA-DR+CD44+) and M2 Macrophages (CD14+CD163+CD206+CD11c+CD11b+HLA-DR+CD44+), all expressing CES-1. Conclusion: We demonstrated specific CES-1 positive myeloid cells within intestinal biopsies, PBMCs of non-responsive patients, and fistulae samples of CD patients. Targeting CES-1+ with ESM-technology could provide new therapeutic targets for CD.